PERTANGGUNGJAWABAN NOTARIS PADA PENERBITAN COVERNOTE - Rahmia Kadir; Farida Patittingi; Nurfaidah Said; Muhammad Ilham Arisaputra (Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractCovernote is a certificate containing the ability of a notary to carry out what the creditor wants. Notary is solely responsible for the content contained in the covernote. In the event of a nonconformity between a statement in covernote and its reality in the field, the notary must be responsible, whether criminal or civil and even morally responsible. A notary's office is a profession that is given great trust and high by society so that what he poured in his legal products or in his explanations can be regarded as something that is true. So, when there is a notary statement that is not in accordance with the actual situation, it will have an impact on tercederainya notary profession itself. IntisariCovernote adalah surat keterangan yang berisikan kesanggupan dari notaris untuk melaksanakan apa yang diinginkan oleh kreditur. Notaris bertanggung jawab penuh atas isi yang dimuat dalam covernote. Ketidaksesuaian yang terjadi antara pernyataan dalam covernote dengan realitas di lapangan, notaris harus bertanggung jawab, baik secara pidana, perdata, ataupun bertanggung jawab secara moral. Jabatan notaris adalah profesi yang diberikan kepercayaan besar dan tinggi oleh masyarakat sehingga apa yang dituangkannya dalam produk hukumnya ataupun pada keterangan-keterangannya dapat dianggap sebagai sesuatu yang benar. Jadi, ketika terdapat pernyataan notaris yang tidak sesuai dengan keadaan yang sebenarnya, maka akan berdampak pada tercederainya profesi notaris itu sendiri.